Mechanism of miR-200b-3p-induced FOSL2 inhibition of endometrial cancer cell proliferation and metastasis - Lijie He; Zhongmin Jiang; Jing Wang; Zhe Han (Scientific Reports)
Abstract The purpose of this study was to investigate how miR-200b-3p inhibits the proliferation and metastasis of endometrial cancer cells by inducing the expression of FOSL2 in the AP1 transcription family. Endometrial cancer cell line HEC-1-A was divided into 16 groups: NC-mimic (transfected with negative control NC mimic), miR-200b-3p mimic (transfected with miR-200b-3p mimic), NC-suppress (transfected with negative control NC inhibit), miR-200b-3p inhibit group (transfected with miR-200b-3p inhibit), si-NC (transfected with negative control si-NC), si-FOSL2 (transfected with Si-FOSL2), oe-NC (transfected with negative control oe-NC), oe-FOSL2 group (oe-FOSL2), miR-200b-3p mimic + oe-NC group (co-transfected with miR-200b-3p mimic and oe-NC), miR-200b-3p mimic + oe-FOSL2 group (co-transfected with miR-200b-3p mimic and oe-FOSL2), miR-200b-3p inhibit + si-NC group (co-transfected with miR-200b-3p inhibit and si-NC), miR-200b-3p inhibit + si-FOSL2 group (co-transfected with miR-200b-3p inhibit and si-FOSL2), miR-200b-3p mimic + si-NC group (co-transfected with miR-200b-3p mimic and si-NC), miR-200b-3p mimic + si-FOSL2 group (co-transfected with miR-200b-3p mimic and si-FOSL2), miR-200b-3p inhibit + oe-NC group (co-transfected with miR-200b-3p inhibit and oe-NC), miR-200b-3p inhibit + oe-FOSL2 group (co-transfected with miR-200b-3p inhibit and oe-FOSL2). Real-time fluorescence quantitative PCR, Western blot, CCK-8 assay, scratch test and Transwell assay were used to detect the expression of miR-200b-3p mRNA, FOSL2 mRNA and protein, cell proliferation, migration and invasion. In endometrial cancer cell lines, the expression of miR-200b-3p was significantly down-regulated (P < 0.05), while the expression of FOSL2 was significantly up-regulated (P < 0.05). Compared with NC-mimic group, the expression of FOSL2, N-cadherin and Vimentin in miR-200b-3p mimic group was significantly decreased (P < 0.05), and the expression of E-cadherin was significantly increased (P < 0.05). The cell proliferation, migration rate and the number of transmembrane cells were significantly decreased (P < 0.05). Compared with the miR-200b-3p mimic + oe-NC group, the expression of FOSL2, N-cadherin and Vimentin in miR-200b-3p mimic + oe-FOSL2 was significantly increased (P < 0.05), the expression level of E-cadherin was significantly decreased (P < 0.05), and the cell proliferation, migration rate and the number of transmembrane cells were significantly increased (P < 0.05). Compared with NC-inhibit group, the expression of FOSL2, N-cadherin and Vimentin in miR-200b-3p inhibit group was significantly increased (P < 0.05), and the expression of E-cadherin was significantly decreased (P < 0.05). The cell proliferation, migration rate and the number of transmembrane cells were significantly increased (P < 0.05). Compared with the miR-200b-3p inhibit + si-NC group, the expression of FOSL2, N-cadherin and Vimentin in miR-200b-3p inhibit + si-FOSL2 was significantly decreased (P < 0.05), and the expression of E-cadherin was significantly increased (P < 0.05); the cell proliferation, migration rate and the number of transmembrane cells were significantly decreased (P < 0.05) The expression of miR-200b-3p in endometrial cancer cells is down-regulated, which can inhibit the proliferation, migration and invasion of endometrial cancer cells by regulating the EMT process, and its mechanism is related to its targeted negative regulation of FOSL2 expression.